LOWER MIOCENE SEDIMENTS OF CENTRAL AND WESTERN CISCAUCASIA - Stolyarov A.S.; Ivleva E.I. (My University, 2006)
The composition, structure, and geochemical properties of the thickest, relatively deep-water Lower Miocene sediments developed in western Ciscaucasia are considered. Of particular interest are materials from the Kuban superdeep borehole SG-12000 that recovered the uppermost layers of the Maikop Group at 3148-3961 m in the central Indol-Kuban Trough west of Krasnodar. However, the borehole did not penetrate the whole Lower Miocene section of the Maikop Group. Therefore, characteristics of the Maikop Group are supplemented with new materials from several other boreholes drilled in the eastern Kuban region. Thus, the typical (reference) Lower Miocene section of central and western Ciscaucasia has been sufficiently well described. © Pleiades Publishing, Inc., 2006.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен